2015
DOI: 10.1093/ijnp/pyv106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ephs and Ephrins in Memory Formation

Abstract: The ability to efficiently store memories in the brain is a fundamental process and its impairment is associated with multiple human mental disorders. Evidence indicates that long-term memory formation involves alterations of synaptic efficacy produced by modifications in neural transmission and morphology. The Eph receptors and their cognate ephrin ligands have been shown to be involved in these key neuronal processes by regulating events such as presynaptic transmitter release, postsynaptic glutamate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 177 publications
(226 reference statements)
1
33
0
Order By: Relevance
“…Our results explicitly delineated that EPHB2 is the most significant altered molecule of Ephrin receptor signaling in the hypothalamus of the LPS-induced depressive phenotype. EPHB2 is not only involved in glutamatergic neurotransmission but also simultaneously participates in the inflammation regulation process in some brain diseases including stroke, anxiety and Alzheimer's disease (Coulthard et al, 2012;Dines and Lamprecht, 2016;Ernst et al, 2019). Cumulatively, our present study and aforementioned studies showed that EPHB2 is intimately involved in inflammationrelated depression.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our results explicitly delineated that EPHB2 is the most significant altered molecule of Ephrin receptor signaling in the hypothalamus of the LPS-induced depressive phenotype. EPHB2 is not only involved in glutamatergic neurotransmission but also simultaneously participates in the inflammation regulation process in some brain diseases including stroke, anxiety and Alzheimer's disease (Coulthard et al, 2012;Dines and Lamprecht, 2016;Ernst et al, 2019). Cumulatively, our present study and aforementioned studies showed that EPHB2 is intimately involved in inflammationrelated depression.…”
Section: Discussionsupporting
confidence: 68%
“…mediates glutamatergic neurotransmission and neuroplasticity in injury and inflammation of the CNS (Coulthard et al, 2012;Wan et al, 2018). The Eph tyrosine kinase receptors were subdivided into 9 EPHA receptors (EPHA1-8 and EPHA10) and 5 EPHB receptors (EPHB1-4 and EPHB6), based on their binding to two subclasses of cognate ligands, Ephrin-As and Ephrin-Bs (Dines and Lamprecht, 2016;Taylor et al, 2017). The EPHB/Ephrin-Bs, which are distributed extensively and provide unique bidirectional signaling between neurons and astrocytes, have attracted considerable attention because of their regulation of neuronal maturation and synaptic plasticity (Koeppen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eph receptor belongs to the ephrin receptor subfamily of the protein-tyrosine kinase family. Eph receptors and ephrins (their ligands) regulate key CNS processes, such as neurotransmitter release, postsynaptic glutamate receptor conductance, synaptic glutamate reuptake, and dendritic spine morphogenesis 48 . They are involved in memory formation 49 and anxiety 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Memory deficits (during episodes and interepisodic) and high anxiety levels (during episodes) are both often reported in BPD. It is therefore of interest that Ephs and ephrins (their ligands) may be pharmacologically targeted 48,51,52 : EphB2-blockade impedes physiological stress responses in wild-type mice 50 . In addition to serving as therapeutic targets, traces of RNAs may serve as markers to monitor disease progression, as has been demonstrated for cancer 47 .…”
Section: Discussionmentioning
confidence: 99%